Providing skilled birth attendants and emergency obstetric care to the poor through partnership with private sector obstetricians in Gujarat, India - Amarjit Singh; Dileep V Mavalankar; Ramesh Bhat; Ajesh Desai; SR Patel; Prabal V Singh; Neelu Singh
PROBLEM: India has the world's largest number of maternal deaths estimated at 117 000 per year. Past efforts to provide skilled birth attendants and emergency obstetric care in rural areas have not succeeded because obstetricians are not willing to be posted in government hospitals at subdistrict level. APPROACH: We have documented an innovative public-private partnership scheme between the Government of Gujarat, in India, and private obstetricians practising in rural areas to provide delivery care to poor women. LOCAL SETTING: In April 2007, the majority of poor women delivered their babies at home without skilled care. RELEVANT CHANGES: More than 800 obstetricians joined the scheme and more than 176 000 poor women delivered in private facilities. We estimate that the coverage of deliveries among poor women under the scheme increased from 27% to 53% between April and October 2007. The programme is considered very successful and shows that these types of social health insurance programmes can be managed by the state health department without help from any insurance company or international donor. LESSONS LEARNED: At least in some areas of India, it is possible to develop large-scale partnerships with the private sector to provide skilled birth attendants and emergency obstetric care to poor women at a relatively small cost. Poor women will take up the benefit of skilled delivery care rapidly, if they do not have to pay for it.